Histological abnormalities in biopsies from macroscopically normal colonoscopies. Issue 3 (March 1986) - Sanderson, I R; Boyle, S; Williams, C B; Walker-Smith, J A
Abstract : One hundred and nineteen children with gastrointestinal symptoms underwent colonoscopy during the course of one year. Out of 39 children that were reported as yielding normal results on endoscopic examination, six had disease detectable only by histology. The pathology included cases of microscopic colitis, Crohn's disease, and indeterminate colitis. To exclude large bowel inflammation as a cause of gastrointestinal symptoms biopsy specimens should always be taken at endoscopy.